AUTONOMOUS DECENTRALIZED DATA CONSISTENCY FOR HIGH-ASSURANCE EMBEDDED SYSTEM - Shiibashi, Akio; Mori, Kinji (International Journal of Computing, 2014)
Advancement in computer and communication technologies have resulted in an explosive growth in embedded systems. The market and users requirements have been rapidly changing and diversified. Under these evolving situations, the assurance to keep the continuous system operation of embedded systems is becoming more and more important. The Autonomous Decentralized System (ADS) has been proposed for resolving the on-line property to achieve the step-by-step expansion, maintenance and fault-propagation prevention for high assurance. This architecture is effective to improve the reliability and reduce the development cost and product cycle time to market by data-driven mechanism. The technologies have been applied in the IC card system for train fare collection and its effectiveness has been proven.